Anti-corrosion scale inhibitor and preparation method thereof
By introducing phosphate polymers into anti-corrosion scale inhibitors, a stable chelate is formed, which solves the problem of degradation of scale inhibition effect under high concentration calcium ions, and achieves high-efficiency scale inhibition performance under a wide range of conditions. It is suitable for industrial use Water treatment.
Patent Information
- Application Number
- CN202411074809.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-27
AI Technical Summary
The existing anticorrosion scale inhibitors are prone to deterioration in high-concentration calcium ion environments, and it is difficult to maintain their effectiveness under a wide range of pH and temperature conditions.
Phosphate polymers are used as anticorrosion polymers, and by introducing phosphate groups directly connected to carbon atoms, a stable chelate reacts with metal ions in water, reducing fouling formation and improving calcium tolerance.
Maintaining effectiveness under a wider range of pH and temperature conditions improves the calcium tolerance and dirt dispersion ability of scale inhibitors, significantly improves scale inhibition performance, and is suitable for industrial water treatment, especially boiler water treatment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of scale inhibitors, and more specifically, to an anti-corrosion and scale inhibitor and a preparation method thereof. Background Art
[0002] Scale is mainly formed by the deposition of minerals in water, such as calcium, magnesium, and silicon, and is commonly found in water treatment systems such as boilers, heat exchangers, pipes, cooling towers, and reverse osmosis membranes. Scale inhibitors have the function of dispersing sparingly soluble inorganic salts in water, preventing or interfering with the precipitation and scaling of sparingly soluble inorganic salts on metal surfaces, and maintaining good heat transfer effects on metal equipment. Among them, anti-corrosion and scale inhibitors have received widespread attention in recent years as an efficient and environmentally friendly water treatment technology. Anti-corrosion and scale inhibitors form a charged layer on the surface of equipment or scale particles, and prevent particles from aggregating through electrostatic repulsion, thereby inhibiting the formation of a scale layer. By adsorbing on the metal surface, a protective film is formed to prevent the metal from contacting corrosive substances, thereby slowing down the corrosion process. However, the current anti-corrosion and scale inhibitors are prone to reduced scale inhibition effects under high concentrations of calcium ions. Summary of the invention
[0003] In view of this, the object of the present invention is to provide an anti-corrosion and anti-scaling agent and a preparation method thereof.
[0004] The anti-corrosion and anti-scaling agent comprises an anti-corrosion polymer, and the anti-corrosion polymer has a structure shown in Formula I or Formula II:
[0005]
[0006] R1 is selected from a sulfonate group or a sulfite group;
[0007] R2 is selected from alkyl, alkoxy, aryl, and heteroaryl.
[0008] Preferably or optionally, the alkane group is C a H 2a+1 , C b H 2b-1 , C c H 2c-3 One of the following, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0009] The alkoxy group is C a H 2a+1 O.C b H 2b-1 O.C c H 2c-3 One of O, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0010] The aryl group is one of phenyl, anthracenyl, naphthyl and biphenyl;
[0011] The heteroaryl group has 1 to 12 carbon atoms.
[0012] Preferably or optionally, the heteroaryl group specifically includes one of pyridyl, indolyl, pyrrolyl, imidazolyl, thienyl, furanyl, 1,2-thiazolyl, 1,3-thiazolylcarbazolyl and naphthiadiazolyl.
[0013] Preferably or optionally, the degree of polymerization n of the anticorrosive polymer is 20-800.
[0014] Preferably or optionally, the anticorrosion and scale inhibitor comprises, by weight: 35-75 parts of anticorrosion polymer, 5-15 parts of polyoxyethylene ether, 10-15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, 10-15 parts of polyepoxysuccinic acid, and 5-30 parts of deionized water.
[0015] Preferably or optionally, the anticorrosive polymer monomer has a structure shown in Formula III or Formula IV:
[0016]
[0017] R1 is selected from a sulfonate group or a sulfite group;
[0018] R2 is selected from alkyl, alkoxy, aryl, and heteroaryl.
[0019] Preferably or optionally, the alkane group is C a H 2a+1 , C b H 2b-1 , C c H 2c-3 One of the following, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0020] The alkoxy group is C a H 2a+1 O.C b H 2b-1 O.C c H 2c-3 One of O, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0021] The aryl group is one of phenyl, anthracenyl, naphthyl and biphenyl;
[0022] The heteroaryl group has 1 to 12 carbon atoms.
[0023] The heteroaryl group specifically includes one of pyridyl, indolyl, pyrrolyl, imidazolyl, thienyl, furyl, 1,2-thiazolyl, 1,3-thiazolylcarbazolyl, and naphthiadiazolyl.
[0024] The present invention also provides a method for preparing an antiscaling agent, comprising the following steps:
[0025] S1: 35-75 parts of anticorrosive polymer and 5-30 parts of deionized water are weighed and added to a reaction kettle in sequence, and stirred at 15-35°C for 0.1-3h;
[0026] S2: Add 5 to 15 parts of polyoxyethylene ether, 10 to 15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 10 to 15 parts of polyepoxysuccinic acid into a reaction kettle, and stir at 30 to 50° C. for 0.5 to 2 hours to obtain the anticorrosion and antiscaling agent.
[0027] The present invention provides an anti-corrosion and scale inhibitor and a preparation method thereof. The anti-corrosion polymer of formula I to II is introduced into the anti-corrosion and scale inhibitor. The anti-corrosion polymer belongs to a phosphate polymer and contains a phosphate group directly connected to a carbon atom. This structure makes the phosphate polymer have high stability and is not easy to hydrolyze into orthophosphate. This stability is a key advantage of the anti-corrosion polymer as a scale inhibitor, because they can maintain effectiveness under a wider range of pH values and temperature conditions, and are not easy to decompose or inactivate. In addition, due to the multi-functional groups contained in its structure, the phosphate polymer can form a stable chelate with the metal ions in the water, thereby effectively preventing the metal ions from reacting with carbonates or sulfates in the water to form precipitation. This chelation effect helps to reduce the formation of scale and can improve the calcium tolerance of the scale inhibitor, that is, the scale inhibition effect can still be maintained in the presence of a higher concentration of calcium ions. It not only has corrosion inhibition performance, but also significantly improves the ability to disperse scale and scale inhibition performance. This type of polymer scale inhibitor has broad application prospects in industrial water treatment, especially in the field of boiler water treatment. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The object of the present invention is to provide an anti-corrosion and scale inhibitor and a preparation method thereof, based on the technical problem that the existing anti-corrosion and scale inhibitor is easily saturated in a high calcium ion environment.
[0030] The anti-corrosion and anti-scaling agent includes an anti-corrosion polymer having a structure shown in Formula I or Formula II:
[0031]
[0032] R1 is selected from a sulfonate group or a sulfite group;
[0033] R2 is selected from alkyl, alkoxy, aryl, and heteroaryl.
[0034] In the present invention, the alkane group is C a H 2a+1 , C b H 2b-1 , C c H 2c-3 One of the following, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0035] Alkoxy is C a H 2a+1 O.C b H 2b-1 O.C c H 2c-3 One of O, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0036] Aryl is one of phenyl, anthracenyl, naphthyl and biphenyl;
[0037] The heteroaryl group has 1 to 12 carbon atoms.
[0038] In the present invention, the heteroaryl group specifically includes one of pyridyl, indolyl, pyrrolyl, imidazolyl, thienyl, furyl, 1,2-thiazolyl, 1,3-thiazolylcarbazolyl and naphthiadiazolyl.
[0039] In the present invention, the polymerization degree n of the anticorrosive polymer is 20-800.
[0040] In the present invention, the antiscalant comprises, by weight: 35-75 parts of antiscalant polymer, 5-15 parts of polyoxyethylene ether, 10-15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, 10-15 parts of polyepoxysuccinic acid, and 5-30 parts of deionized water.
[0041] In the present invention, the anticorrosive polymer monomer has a structure shown in Formula III or Formula IV:
[0042]
[0043] R1 is selected from a sulfonate group or a sulfite group;
[0044] R2 is selected from alkyl, alkoxy, aryl, and heteroaryl.
[0045] In the present invention, the alkane group is C a H 2a+1 , C b H 2b-1 , C c H 2c-3 One of the following, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0046] Alkoxy is C a H 2a+1 O.C b H 2b-1 O.C c H 2c-3 One of O, wherein 0<a≤6, 0<b≤6, 0<c≤6;
[0047] Aryl is one of phenyl, anthracenyl, naphthyl and biphenyl;
[0048] The heteroaryl group has 1 to 12 carbon atoms.
[0049] The heteroaryl group specifically includes one of pyridyl, indolyl, pyrrolyl, imidazolyl, thienyl, furyl, 1,2-thiazolyl, 1,3-thiazolylcarbazolyl, and naphthiadiazolyl.
[0050] The present invention also provides a method for preparing an antiscaling agent, comprising the following steps:
[0051] S1: 35-75 parts of anticorrosive polymer and 5-30 parts of deionized water are weighed and added to a reaction kettle in sequence, and stirred at 15-35°C for 0.1-3h;
[0052] S2: Add 5 to 15 parts of polyoxyethylene ether, 10 to 15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 10 to 15 parts of polyepoxysuccinic acid into the reactor, and stir at 30 to 50°C for 0.5 to 2 hours to obtain an anticorrosion and scale inhibitor. By introducing the anticorrosion polymers of formulas Ⅰ to Ⅱ into the anticorrosion and scale inhibitor, the anticorrosion polymers belong to phosphate polymers and contain phosphate groups directly connected to carbon atoms. This structure makes the phosphate polymers have high stability and are not easily hydrolyzed into orthophosphates. This stability is a key advantage of the present anticorrosion polymers as scale inhibitors because they can maintain effectiveness under a wider range of pH and temperature conditions without being easily decomposed or inactivated. In addition, due to the multi-functional groups contained in their structure, phosphate polymers can form stable chelates with metal ions in water, thereby effectively preventing metal ions from reacting with carbonates or sulfates in water to form precipitation. This chelation effect helps reduce the formation of scale and can improve the calcium tolerance of the scale inhibitor, that is, it can still maintain the scale inhibition effect in the presence of higher concentrations of calcium ions. It not only has corrosion inhibition performance, but also significantly improves the ability to disperse scale and scale inhibition performance. This type of polymer scale inhibitor has broad application prospects in industrial water treatment, especially in boiler water treatment and other fields.
[0053] Preparation Example
[0054] A) Synthesis of cyclization precursors:
[0055] 4 mol of ethylene glycol and 8 mol of triethylamine were added to the reactor in sequence. The temperature of the reaction system was controlled at 5°C. At this temperature, 4 mol of phosphorus trichloride was gradually added while stirring continuously. The reaction mixture was stirred for 6 hours at room temperature. After stirring, the white precipitate of triethylamine hydrochloride was removed by filtration. Next, after multiple vacuum distillation and washing steps, the cyclized precursor was finally obtained.
[0056] B) Synthetic anticorrosive monomers
[0057] 4 mol of benzenesulfonic acid and 4 mol of triethylamine were added to the reactor in sequence. The temperature of the reaction system was controlled at 5°C. At this temperature, 4 mol of the cyclization precursor was gradually added while stirring continuously. The reaction mixture was stirred for 6 hours at room temperature. After stirring, filtration was performed to remove the generated white precipitate of triethylamine hydrochloride. Next, after multiple vacuum distillation and washing steps, the antiseptic monomer was finally obtained.
[0058] C) Preparation of anticorrosive polymers
[0059] 2 mol of anticorrosive monomer and 0.08 mol of AIBN were added into the reactor in sequence, and the mixture was stirred and reacted at 80° C. for 3 h to prepare an anticorrosive polymer.
[0060] Example 1
[0061] Anticorrosive polymer degree of polymerization: n = 50
[0062] Anticorrosive polymer: 50 parts
[0063] Polyoxyethylene ether: 10 parts
[0064] Maleic anhydride-acrylic acid-polyoxyethylene ether copolymer: 12 parts
[0065] Polyepoxysuccinic acid: 13 parts
[0066] Deionized water: 25 parts
[0067] Heteroaryl: pyridyl
[0068] Preparation method:
[0069] S1: 50 parts of anticorrosive polymer and 25 parts of deionized water were added into a reaction kettle and stirred at 20°C for 1 hour.
[0070] S2: Add 10 parts of polyoxyethylene ether, 12 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 13 parts of polyepoxysuccinic acid, and stir at 40° C. for 1 hour to obtain an anticorrosion and antiscaling agent.
[0071] Example 2
[0072] Anticorrosive polymer degree of polymerization: n = 300
[0073] Anticorrosive polymer: 45 parts
[0074] Polyoxyethylene ether: 7 parts
[0075] Maleic anhydride-acrylic acid-polyoxyethylene ether copolymer: 11 parts
[0076] Polyepoxysuccinic acid: 14 parts
[0077] Deionized water: 15 parts
[0078] Heteroaryl: indolyl
[0079] Preparation method:
[0080] S1: 45 parts of anticorrosive polymer and 15 parts of deionized water were added into a reaction kettle and stirred at 30°C for 2 hours.
[0081] S2: Add 7 parts of polyoxyethylene ether, 11 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 14 parts of polyepoxysuccinic acid, and stir at 45°C for 1.5 hours.
[0082] Example 3
[0083] Anticorrosive polymer degree of polymerization: n = 200
[0084] Anticorrosive polymer: 60 parts
[0085] Polyoxyethylene ether: 5 parts
[0086] Maleic anhydride-acrylic acid-polyoxyethylene ether copolymer: 10 parts
[0087] Polyepoxysuccinic acid: 10 parts
[0088] Deionized water: 10 parts
[0089] Heteroaryl: pyrrolyl
[0090] Preparation method:
[0091] S1: 60 parts of anticorrosive polymer and 10 parts of deionized water were added into a reaction kettle and stirred at 25°C for 0.5 hours.
[0092] S2: Add 5 parts of polyoxyethylene ether, 10 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 10 parts of polyepoxysuccinic acid, and stir at 35° C. for 1 hour.
[0093] Example 4
[0094] Anticorrosive polymer degree of polymerization: n = 450
[0095] Anticorrosive polymer: 35 parts
[0096] Polyoxyethylene ether: 15 parts
[0097] Maleic anhydride-acrylic acid-polyoxyethylene ether copolymer: 15 parts
[0098] Polyepoxysuccinic acid: 10 parts
[0099] Deionized water: 20 parts
[0100] Heteroaryl: imidazolyl
[0101] Preparation method:
[0102] S1: 35 parts of anticorrosive polymer and 20 parts of deionized water were added into a reaction kettle and stirred at 15°C for 3 hours.
[0103] S2: Add 15 parts of polyoxyethylene ether, 15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 10 parts of polyepoxysuccinic acid, and stir at 50° C. for 2 hours.
[0104] Example 5
[0105] Anticorrosive polymer degree of polymerization: n = 800
[0106] Anticorrosive polymer: 70 parts
[0107] Polyoxyethylene ether: 5 parts
[0108] Maleic anhydride-acrylic acid-polyoxyethylene ether copolymer: 10 parts
[0109] Polyepoxysuccinic acid: 10 parts
[0110] Deionized water: 5 parts
[0111] Heteroaryl: thienyl
[0112] Preparation method:
[0113] S1: 70 parts of anticorrosive polymer and 5 parts of deionized water were added into a reaction kettle and stirred at 35°C for 2 hours.
[0114] S2: Add 5 parts of polyoxyethylene ether, 10 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 10 parts of polyepoxysuccinic acid, and stir at 40° C. for 1 hour.
[0115] Comparative Example 1
[0116] The blank control was used as comparative example 1.
[0117] The scale inhibition performance of the anti-corrosion and scale inhibitor prepared in each example and the comparative example was tested to evaluate its slow release effect and scale inhibition efficiency in the simulated water treatment system. The scale inhibition performance of the anti-corrosion and scale inhibitor on CaCO3 was determined by the static scale inhibition method with reference to GB / T 16632-2008 "Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method".
[0118] Potassium hydroxide solution: 200g / L
[0119] Borax buffer solution: pH ≈ 9, weigh 3.80 g of sodium tetraborate decahydrate (Na2B4O7, ·10H2O), dissolve it in water and dilute to 1 L.
[0120] Sodium bicarbonate standard solution: 1mL contains about 18.3mgHCO3 - :, prepare and calibrate according to the following steps:
[0121] a) Preparation: Weigh 25.2 g of sodium bicarbonate into a 100 mL beaker, dissolve in water, transfer all to a 1000 mL volumetric flask, dilute to scale with water, and shake well. The solution is prepared before use.
[0122] b) Calibration: Pipette 5.00 mL of sodium bicarbonate standard solution into a 250 mL conical flask, add about 50 mL of water and 3 to 5 drops of bromocresol green-methyl red indicator solution, and titrate with hydrochloric acid standard titration solution until the solution changes from light blue to purple, which is the end point.
[0123] c) Calculation: Bicarbonate ion (HCO3 - ) content is calculated as mass concentration ρ1 according to formula (1):
[0124] ρ1=V1cM / V Formula (1)
[0125] In formula (1):
[0126] ρ1-Bicarbonate ion (HCO3 - ) mass concentration, in milligrams per milliliter (mg / mL);
[0127] V1-the volume of the hydrochloric acid standard titration solution consumed in the titration, in milliliters (mL);
[0128] c-The accurate value of the actual concentration of the hydrochloric acid standard titration solution, in moles per liter (mol / L);
[0129] M-bicarbonate ion (HCO3 - ) The numerical value of the molar mass in grams per mole (g / mol)
[0130] (M=61.00);
[0131] V-the volume of the sodium bicarbonate standard solution taken, in milliliters (mL) (V=5).
[0132] Preparation of test solution
[0133] Water treatment agent sample solution: 1.00 mL contains 0.500 mg of water treatment agent (on a dry basis).
[0134] Water for actual working conditions: Add 250mL of test water sample to a 500mL volumetric flask, add a certain amount of water treatment agent sample solution with a pipette, shake well, dilute to scale with water, and shake well.
[0135] Prepare water: Add 250mL of water to a 500mL volumetric flask, and use a burette to add a certain volume of calcium chloride standard solution to make the amount of calcium ions 120mg. Use a pipette to add a certain amount of water treatment agent sample solution and shake well. Then add 20mL of borax buffer solution and shake well. Use a burette to slowly add a certain volume of sodium bicarbonate standard solution (shaking while adding) to make the amount of bicarbonate ions 366mg, dilute with water to the scale, and shake well.
[0136] The scale inhibition performance of water treatment agents is expressed in η and the value is expressed in %, which is calculated according to formula (2):
[0137] η=(ρ4-ρ3) / (ρ-ρ3) Formula (2)
[0138] In formula (2):
[0139] ρ4-Calcium ions (Ca 2+ ) is the mass concentration value in milligrams per milliliter (mg / mL);
[0140] ρ3-Calcium ion (Ca) after blank test solution without water treatment agent 2+ ) is the mass concentration value in milligrams per milliliter (mg / mL);
[0141] ρ-Calcium ions (Ca 2+ ) is the mass concentration value in milligrams per milliliter (mg / mL).
[0142] Table 1 below shows the scale inhibition performance parameters of the water treatment agent for each example and comparative example
[0143] Table 1
[0144] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 η 89.8% 93.1% 92.9% 96.7% 94.0% 78.8%
[0145] It can be seen from the above table that the scale inhibitors of the embodiments of the present application have much higher scale inhibition performance parameters for water treatment agents than the comparative examples. The embodiments of the present invention introduce phosphate polymer segments into the anti-corrosion and scale inhibitors, and the phosphate polymers have a higher stability with a phosphate structure, and are not easily hydrolyzed into orthophosphates. This stability is a key advantage of the anti-corrosion segments as scale inhibitors, because they can maintain effectiveness under a wider range of pH values and temperature conditions, and are not easily decomposed or inactivated. In addition, due to the multi-functional groups contained in their structure, phosphate polymers can form stable chelates with metal ions in water, thereby effectively preventing metal ions from reacting with carbonates or sulfates in water to form precipitation. This chelation effect helps to reduce the formation of scale and can improve the calcium tolerance of the scale inhibitor, that is, the scale inhibition effect can still be maintained in the presence of higher concentrations of calcium ions. It not only has corrosion inhibition performance, but also significantly improves the dispersion ability and scale inhibition performance of scale.
[0146] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. An antiscaling agent, characterized in that: The antiscalant comprises an antiscalant polymer having a structure shown in Formula I or Formula II: R1 is selected from a sulfonate group or a sulfite group; R2 is selected from alkyl, alkoxy, aryl, and heteroaryl.
2. The antiscaling agent according to claim 1, characterized in that: The alkane group is C a H 2a+1 , C b H 2b-1 , C c H 2c-3 One of the following, wherein 0<a≤6, 0<b≤6, 0<c≤6; The alkoxy group is C a H 2a+1 O.C b H 2b-1 O.C c H 2c-3 One of O, wherein 0<a≤6, 0<b≤6, 0<c≤6; The aryl group is one of phenyl, anthracenyl, naphthyl and biphenyl; The heteroaryl group has 1 to 12 carbon atoms.
3. The antiscaling agent according to claim 2, characterized in that: The heteroaryl group specifically includes one of pyridyl, indolyl, pyrrolyl, imidazolyl, thienyl, furyl, 1,2-thiazolyl, 1,3-thiazolylcarbazolyl, and naphthiadiazolyl.
4. The antiscaling agent according to claim 1, characterized in that: The polymerization degree n of the anticorrosive polymer is 20-800.
5. The antiscaling agent according to claim 1, characterized in that: In terms of weight, the antiscalant includes: 35-75 parts of antiscalant polymer, 5-15 parts of polyoxyethylene ether, 10-15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, 10-15 parts of polyepoxysuccinic acid, and 5-30 parts of deionized water.
6. The antiscaling agent according to claim 5, characterized in that: The anticorrosive polymer monomer has a structure shown in Formula III or Formula IV: R1 is selected from a sulfonate group or a sulfite group; R2 is selected from alkyl, alkoxy, aryl, and heteroaryl.
7. The antiscaling agent according to claim 6, characterized in that: The alkane group is C a H 2a+1 , C b H 2b-1 , C c H 2c-3 One of the following, wherein 0<a≤6, 0<b≤6, 0<c≤6; The alkoxy group is C a H 2a+1 O.C b H 2b-1 O.C c H 2c-3 One of O, wherein 0<a≤6, 0<b≤6, 0<c≤6; The aryl group is one of phenyl, anthracenyl, naphthyl and biphenyl; The heteroaryl group has 1 to 12 carbon atoms.
8. The antiscaling agent according to claim 6, characterized in that: The heteroaryl group specifically includes one of pyridyl, indolyl, pyrrolyl, imidazolyl, thienyl, furyl, 1,2-thiazolyl, 1,3-thiazolylcarbazolyl, and naphthiadiazolyl.
9. A method for preparing an antiscaling agent, characterized in that: The following steps are involved: S1: 35-75 parts of anticorrosive polymer and 5-30 parts of deionized water are weighed and added to a reaction kettle in sequence, and stirred at 15-35°C for 0.1-3h; S2: Add 5 to 15 parts of polyoxyethylene ether, 10 to 15 parts of maleic anhydride-acrylic acid-polyoxyethylene ether copolymer, and 10 to 15 parts of polyepoxysuccinic acid into a reaction kettle, and stir at 30 to 50° C. for 0.5 to 2 hours to obtain the anticorrosion and antiscaling agent.
10. Use of the anti-corrosion and scale inhibitor according to any one of claims 1 to 8 or the preparation method of the anti-corrosion and scale inhibitor according to claim 9 in anti-corrosion and scale inhibitors.